Parent–child attachment and mental health in young adolescents: a moderated mediation analysis - Tan, Rong; Yang, Yizhi; Huang, Tao; Lin, Xuanxuan; Gao, Hua (Frontiers in Psychology, 2023)
The parent-child attachment has a significant impact on adolescents' mental health. However, the influence of psychological quality and coping styles on this connection remains unknown. This study examined the relationship between parent-child attachment and adolescent mental health, by exploring the mediating role of psychological quality and the moderating role of coping styles. A total of 633 young adolescents participated in this study after signing informed consent. They anonymously completed questionnaires including the Parent and Peer Attachment Scale (Parent Attachment Section), the Coping Styles Inventory for Middle School Students, the Brief Version of the Psychological Quality Inventory for Middle School Students, and the Chinese Middle School Students' Psychological Quality Inventory. After controlling for gender, grade, left-behind category, only-child status, and family structure, the moderated mediation model yielded the following findings: (a) parent-child attachment significantly and positively predicted adolescents' mental health.; (b) psychological quality partially mediated the relationship between parent-child attachment and adolescents' mental health; (c) the association between psychological quality and mental health was moderated by task-focused coping. This moderation effect was more substantial for students with low task-focused coping behaviors, which aligns with the "exclusionary hypothesis" model. Therefore, our results indicate that parent-child attachment indirectly impacts mental health, influenced by internal and external factors. These findings carry significant implications for safeguarding and promoting adolescents' mental well-being.